Changes in the Brazilian foreign policy towards the United States at the beginning of the 21st century: from accommodation to soft balancing - Santos, Leandro Wolpert dos (2019)
The aim of this article is to describe and analyze the main changes that occurred in Brazilian foreign policy towards the United States with the alternation of the Fernando Henrique Cardoso and Lula da Silva governments in the beginning of the 21st century. In this paper, two central arguments are defended. First, that the main changes that occurred in the period were in the objectives: while Cardoso's foreign policy had as its main objective to bring Brazil closer to the hegemonic power, Lula sought to balance power relations with the US, aiming at the construction of a multipolar international order. Second, that both systemic and domestic factors contributed to the occurrence of these changes. Among the first, the following stand out: i) the reorientation of US foreign policy at the turn of the 20th to the 21st century; ii) gradual changes in the global distribution of power during the first decade of the 21st century; and (iii) the rise of left-of-center governments in South America. Domestic factors include: (i) the restructuring of Brazilian domestic policy that began with the 1999 financial crisis and consolidated with the 2002 presidential elections; ii) the reorientation of specific groups within the Itamaraty; and iii) the rise of Lula to the presidency of the Republic.